2008
DOI: 10.1037/1040-3590.20.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Invariance and convergent and discriminant validity between mothers' and fathers' ratings of oppositional defiant disorder toward adults, ADHD-HI, ADHD-IN, and academic competence factors within Brazilian, Thai, and American children.

Abstract: Confirmatory factor analysis was used to test the invariance of an oppositional defiant disorder toward adults, attention-deficit/hyperactivity disorder-hyperactivity/impulsivity, attention-deficit/hyperactivity disorder-inattention, and an Academic Competence factor model between mothers' and fathers' ratings within Brazilian (n = 894), Thai (n = 2,075), and American (n = 817) children with the Child and Adolescent Disruptive Behavior Inventory (G. L. Burns, T. Taylor, & J. Rusby, 2001a, 2001b). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 27 publications
8
47
0
Order By: Relevance
“…In contrast, the explanation in terms of the bias hypothesis means that there is little or no equivalency across the different respondent groups. Thus the support in the Burns et al (2008) study for equivalency in father ratings and mother ratings is more in line with the situational specificity hypothesis.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…In contrast, the explanation in terms of the bias hypothesis means that there is little or no equivalency across the different respondent groups. Thus the support in the Burns et al (2008) study for equivalency in father ratings and mother ratings is more in line with the situational specificity hypothesis.…”
supporting
confidence: 75%
“…These included configural equivalency (same factor structure and the same items associated with the factors), metric equivalency (same strength of the associations of items with the factors, ascertained by equivalency in factor loadings), scalar equivalency (equivalency in item intercepts values), error variance or uniqueness equivalency (equivalency in the error variance of the items or variance of the items not attributed to the underlying construct), equivalency for construct variance (equivalency in the variability of the latent factors), equivalency for construct covariance (equivalency in the strength of the relationships of the latent factors), and equivalency for construct mean scores (equivalency in the mean for the latent factors). For the three samples (US, Brazilian and Thai) examined, the Burns et al (2008) study found support for all these forms of equivalencies for the CADBI (Burns et al 2001).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…reports across children in different countries (Thailand, Brazil, North America, Australia, Malaysia) (Burns, et al, 2008;Burns, Desmul, Walsh, Silpakit, & Ussahawanitchakit, 2009) and across ages 9 to 16 (Sterba, et al, 2010). Measurement invariance across sex has also been demonstrated for American and Malaysian children (and boys scored higher than girls) (Burns, Walsh, Gomez, & Hafetz, 2006).…”
Section: Discussionmentioning
confidence: 88%